The Regional Enlarged Observability for Hilfer Fractional Differential Equations - Abu Bakr Elbukhari; Zhenbin Fan; Gang Li (Axioms, 2023)
In this paper, we investigate the concept of regional enlarged observability (ReEnOb) for fractional differential equations (FDEs) with the Hilfer derivative. To proceed this, we develop an approach based on the Hilbert uniqueness method (HUM). We mainly reconstruct the initial state <semantics><msubsup>ν01</msubsup></semantics> on an internal subregion <semantics>ω</semantics> from the whole domain <semantics>Ω</semantics> with knowledge of the initial information of the system and some given measurements. This approach shows that it is possible to obtain the desired state between two profiles in some selective internal subregions. Our findings develop and generalize some known results. Finally, we give two examples to support our theoretical results.